Increasing the level of methodological training of physical education university students in a student fitness club - Saykina E.G. ,; Kuzmina S.V. ,; Zagryadskaya O.V. ,; Lupanova E.S. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to substantiate the possibilities of organizing a student fitness club during extracurricular hours in a university environment and the conditions for undergoing industrial teaching practice, developing professional competencies, increasing methodological preparedness, and developing the pedagogical skills of students. Methods and structure of the study. To achieve the goal, theoretical methods (analysis of scientific and methodological literature, programs, design) and empirical methods (questionnaires, expert assessment, self-assessment) were used. The study took place on the basis of the Institute of Physical Culture and Sports of the Russian State Pedagogical University named after. A. I. Herzen (IFKiS). It was attended by 1,358 1st-4th year undergraduate and 1st-2nd year master's students of full-time and part-time studies in various areas of training, 350 specialists and students of advanced training courses in physical education and fitness. Results and conclusions. Analysis of studies by many authors (N.V. Kazakevich, 1999; T.S. Lisitskaya, L.V. Sidneva, 2002; V.A. Rostova, M.O. Stupkina, 2003; Yu.V. Streletskaya, 2007, etc.) made it possible to identify a number of main difficulties that students and specialists have encountered since the late 1990s in conducting classes in various areas of aerobics and fitness. According to many authors, the most typical difficulties of physical education teachers and students include: selection of exercises to compose them into combinations, complexes and musical accompaniment for them; methods of teaching new exercises; pedagogical control over the well-being of students and an individual approach. Aerobics experts note that the most significant group of difficulties includes a lack of practical experience, the ability to improvise (lack of motor reserve), and regulate physical activity. Other authors identify a group of problems associated with the level of musical and rhythmic training of specialists, their ability to select music in accordance with the objectives of the lesson, and insufficient knowledge of verbal and non-verbal forms of communication (voice, gestures and facial expressions). The effectiveness of the participation of students and undergraduates in the activities of the SFC will be determined by increasing the level of their theoretical knowledge, methodological training, practical skills, and the formation of their professional competencies.